Forensic and pharmaceutical study of problems turnover of energy drink among young people - Derkach, Anatoliy (Actual Problems of Medicine and Pharmacy, 2021)
Outlined the problem of abuse in youth energy drinks. Powered prevention of youth drug addiction in energy drinks.